APLIKASI MARKETPLACE UNTUK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) MENGGUNAKAN FRAMEWORK LARAVEL - Emir Sasmita; Tristiyanto Tristiyanto (Jurnal Pepadun, 2021)
Micro, Small and Medium Enterprises (MSMEs) have an important and strategic role in national economic development. In the era of globalization, advances in science and technology have brought changes in the business world. Marketplace is an application that bridges sellers and customers to transact virtually. By applying the concept of business to cunsomer (B2C), marketplace facilitates business activities in the network with hundreds of stores available and selling each product to customers. Customers can also have a membership in the store. In addition, stores or MSME units can open branches of business in the marketplace, and utilize universal product data to minimize data differences in the descriptions between products sold by one store and similar products sold by other stores.The marketplace application for MSMEs is built on web based using Laravel framework. The method applied in developing applications is using the waterfall model. The marketplace application for MSMEs has been successfully built by testing functionality using black box testing and showing the results that the application can function according to expectations and user needs.